The Impact of the Use of Creative Accounting Techniques and Practices on the Financial Position and Performance of Economic Entities – Theoretical and Applied Particularities - Mangu (Giurea), Gabriela; Zuca, Marilena Roxana; Soare, Georgiana Janina; Ciobota, Emanuel Catalin; Danescu, Magdalena Gratiela (The Journal of Accounting and Management, 2023)
The theoretical approach of creative accounting techniques and practices captures the way in which the accounting information that characterizes the financial position and performance of the economic entity is influenced. The presentation of the numerous typologies of techniques and practices specific to creative accounting is necessary for all categories of users of financial-accounting information because in this way their effects on the annual financial statements are (re)known and economic decisions are made in the knowledge of the case.